Forecasts of Lithuanian Money Market - Mačiekus, Venantas (Ekonomika, 1995)
Both postcommunist neighbouring countries – Poland ant Lithuania have very similar trajectories of their economical development However, Lithuanian economics lags for about three years behind Poland economics. Besides that, Lithuanian drop in production is deeper than in Poland. The outlined similarity gives an opportunity to use indicators of Poland economics for Lithuanian economical forecast, including Lithuanian money market The comparative analysis of interest rates in both countries enables to draw a conclusion about their close correspondence with three years lag. Thus we can expect that the interest rates in Lithuanian money market in 1995 and 1996 will be the same ar these indicators were in Poland in 1992 and 1993 accordingly.